2015
DOI: 10.1139/cjfr-2015-0106
|View full text |Cite
|
Sign up to set email alerts
|

Response of conifer species from three latitudinal populations to light spectra generated by light-emitting diodes and high-pressure sodium lamps

Abstract: Light-emitting diode (LED) technology shows promise for supplementing photosynthetically active radiation (PAR) in forest nurseries because of the potential reduction in energy consumption and an ability to supply discrete wavelengths to optimize seedling growth. Our objective was to examine the effects of light spectra supplied by LED and traditional high-pressure sodium (HPS) lamps on growth and physiology of Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) and Engelmann spruce (Picea engelmannii Parry ex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 43 publications
6
34
3
Order By: Relevance
“…In other species, leaf biomass was promoted by the LED lighting in Norway spruce seedlings [25] compared to HPS lighting. Leaf biomass was unaffected or negatively impacted by LED lighting relative to the HPS lighting in Scots pine, Douglas-fir, and Engelmann spruce seedlings [20,24]. In our study, neither stem biomass nor root biomass responded to the treatments, indicating that treatments did not drive biomass allocation.…”
Section: Biomass Accumulation and Translocationcontrasting
confidence: 66%
See 4 more Smart Citations
“…In other species, leaf biomass was promoted by the LED lighting in Norway spruce seedlings [25] compared to HPS lighting. Leaf biomass was unaffected or negatively impacted by LED lighting relative to the HPS lighting in Scots pine, Douglas-fir, and Engelmann spruce seedlings [20,24]. In our study, neither stem biomass nor root biomass responded to the treatments, indicating that treatments did not drive biomass allocation.…”
Section: Biomass Accumulation and Translocationcontrasting
confidence: 66%
“…Most of the current studies did not find any response of RCD to the light spectra between HPS and LED lightings [19,20,24,25]. In studies on highly valued slowly-growing seedlings, there was also a rare RCD response found for the HPS lighting relative to the control [5,6].…”
Section: Seedling Shoot Growthcontrasting
confidence: 58%
See 3 more Smart Citations